Competition advocacy for enterprises - Садюк, Андрій (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
Reforms in many industries and business fields in Ukraine need application of modern political tools. One among principles of domestic policy of Ukraine as a state is development of competition and support of efficient control over natural monopolies and prevention of monopolism on markets. Legal confirmation of any economic policy will be carried out by definition of the domestic policy principles. Antimonopoly-competitive policy is one among the focal points of the economic policy in particular. Competition advocacy according to generally accepted approach is a part of such competitive policy; therefore, definition and interpretation of the advocacy competition will affect the contents of the antimonopoly-competitive policy of the government in general and its application in competing industries in most cases, and in particular application with respect to transport. Analysis of scientific publications dedicated to the competition advocacy in Ukraine reveals a variety of interpretations of this notion and arising numerous ambiguities in the content as a result. The article contemplates the meaning of some notions similar to advocacy such as lobbing, informative-educational activities, fundraising. Contents of notions ‘advocacy competition’ and ‘advocacy’ are compared. The foregoing allows us to interpret the content and to show difference between competition advocacy and other notions. Definition of the antimonopoly-competitive policy in legislation is considered together with available activities constituting competition advocacy among the tasks of an anti-monopoly authority in Ukraine. It is considered also whether the governmental bodies are charged with tasks on initiation and organisation of competitive environment in the wide sense of these words. Ambiguous content of the competition advocacy definition in Ukraine is complicated with non-availability of any normative definition of this notion in Ukrainian legislation. Study of the notion ‘competition advocacy’ will allow us to make a conclusion on the possibility of its application in many industries of national economy and in railway transport in particular.